Tuning the Mechanical and Electric Properties of Conjugated Polymer Semiconductors: Side‐Chain Design Based on Asymmetric Benzodithiophene Building Blocks. (24th August 2022) - Liu, Deyu; Lei, Yusheng; Ji, Xiaozhou; Wu, Yilei; Lin, Yangju; Wang, Yunfei; Zhang, Song; Zheng, Yu; Chen, Yuelang; Lai, Jian‐Cheng; Zhong, Donglai; Cheng, Hao‐Wen; et al.
Abstract: Understanding molecular design rules for stretchable polymer semiconductors is important for enabling next generation stretchable electronic circuits. To simultaneously improve both electrical properties and mechanical stretchability, a design strategy is reported in introducing conjugated rigid fused‐rings with bulky side groups in semiconducting polymers. In this work, the understanding of this design concept is improved by systematically investigating the effect of different types of bulky side groups asymmetrically substituted on conjugated polymer semiconductor backbones. Specifically, four types of side groups are investigated, including naphthalene (NaPh), biphenyl (PhPh), thienylphenyl (ThPh), and alkylphenyl (C4Ph), asymmetrically substituted on benzodithiophene units, namely asy‐BDT. With the four types of side groups installed on BDT‐containing conjugated polymers in an asymmetrical fashion, it is observed that they reduced the polymer chain aggregation and film crystallinity, hence improving the film stretchability. Furthermore, the fully conjugated polymer backbone allows maintenance of good charge carrier mobilities. Specifically, polymer PDPP‐C4Ph (with C4Ph side groups) shows the highest mobility in the fully stretchable transistor and maintained its mobility even after being subjected to hundreds of stretching‐releasing cycles at 25% strain. Overall, the results provide anunderstanding of the use of asymmetrically substituted fused‐ring conjugated polymer structures to tune mechanical and charge transport properties. Abstract : The effects of four asymmetric benzodithiophene (asy‐BDT) units with different side groups including naphthalene (NaPh), biphenyl (PhPh), thienylphenyl (ThPh), and alkylbenzene (C4Ph) are investigated in the mechanical and electrical properties of polymer semiconductors. These asy‐BDT units enable to tune the mechanical properties. Meanwhile, introducing these units can ensure conjugation along polymer backbone, which help to maintain high mobility.